“La Política Criminal Ecuatoriana, Frente a un Estado Punitivo Sancionador, Contradice el Estado Constitucional de Derechos y Justicia, Violentando el Principio de Mínima Intervención Penal” - Armijos Reyes, Vagner Armando (2019)
The great transition given in the model of the Ecuadorian State, by coupling with a Constitutional State of rights and justice, with the entry into force of the 2008 Constitution, opened a guaranteed panorama of fundamental rights, especially by establishing the hierarchically superior norm as a legal advance in rights, is so that the judicial proceedings are due to a humanistic line, likewise the special laws that dominate the control of coexistence in society and state policies in the same way, spending 6 years, a Penal Code was repealed sanctioner, who was left behind, giving legal life to a new and improved criminal system, on August 10, 2014 came into force the Organic Comprehensive Criminal Code, which for many writers and legal experts, should be a regulatory breakthrough in criminal matters, resulting in a punitive Penal Code, whose purpose is the sanction of the offender, but not rehabilitation or reintegration into society. the age of the person who has already served his sentence, it is so that a number of legislative options have been given within our Ecuadorian State, in order to purge the society of those who alter the order established morally by them. The Constitutional State of rights and justice, within its most powerful legal norm, establishes rights and equality for all those who integrate it, consecrates principles, duties, obligations and others, but as a result of the increase of criminality, criminal acts of vandalism, it is seen forced to act, but without first specifying a specific objective to combat, or is that perhaps the person member of a society, and was born with the instinct to commit a crime, this criminal normative shooting, which sanctions the antisocial act, justified by the punitive power of the State, is presented as the only exception presumably studied by those who typify their criteria in criminal law. That is why, the purpose of this research work is to conduct a legal, doctrinal and reality study of Ecuadorian society, so that it is possible to clarify that both the Constitutional State of rights and justifies the Criminal adopted by the same and the principles established in the Ecuadorian Magna Carta, as the minimum criminal intervention, are violated by the alleged magic solution that combats the increase in crime, which is the punitive power of the State, translated into an increase in penal sanctions already established, thus placing an endless number of possibilities aside from the idea that only sanctions of a penal nature rehabilitate or cure society, leaving aside extra-cellular mechanisms, and detracting from the value of studying social environment, area of parenting, education, economic situation of the offender, because not only the criminal act is worthy of all attention It should be taken in full consideration the environment in which a possible offender of the criminal law develops and thus, reform, propose and present projects in the fields of education, health, economy, etc., to improve and guarantee the Constitutional State of rights, which promotes a dignified life and a good living for all within society.